Sex, metabolism and health - Adriana Maggi; Sara Della Torre (Elsevier, 2018)
Background: Epidemiological and clinical studies have largely demonstrated major differences in the prevalence of metabolic disorders in males and females, but the biological cause of these dissimilarities remain to be elucidated. Mammals are characterized by a major change in reproductive strategies and it is conceivable that these changes subjected females to a significant evolutionary pressure that perfected the coupling between energy metabolism and reproduction. Scope of review: This review will address the plausibility that female liver functions diverged significantly from males given the role of liver in the control of metabolism. Indeed, it is well known that the liver is sexually dimorphic, and this might be relevant to explain the lower susceptibility to hepatic diseases and liver-derived metabolic disturbances (such as the cardiovascular diseases) characteristic of females during their fertile period. Furthermore, estrogens and the hepatic ERα play a significant role in liver sexual-specific functions and in the control of metabolic functions. Conclusions: A better grasp of the role of male and female sex steroids in the liver of the two sexes may therefore represent an important element to conceive novel treatments aimed at preventing metabolic diseases particularly in ageing women or limiting undesired side effect in the treatment of gender dysphoria. Keywords: Sex, Health